Dead molluscan shells from multiple trophic groups as archives of nitrogen isotopic evidence of wastewater gradients in estuaries. (April 2023) - Carden, Lilja; Lloret, Javier; Kidwell, Susan M.
Abstract: Increased coastal urbanization worldwide has resulted in increased nitrogen inputs to ecosystems, leading to eutrophication and other negative effects. We assessed δ 15 N in the dead-collected shells of three molluscan species in two estuaries in order to evaluate their ability to identify known gradients in wastewater nitrogen input, namely from private septic systems feeding directly into Waquoit Bay and from a groundwater plume reflecting wastewater injection at a municipal treatment plant in West Falmouth Harbor, Massachusetts, USA. Shells of a suspension-feeder ( Geukensia demissa ), a micro-algal grazer ( Littorina littorea ), and an omnivore ( Nassarius obsoletus ) were collected from lower intertidal sediments near the taxon's life habitat. We found that δ 15 N in dead-collected shells decreased significantly along the gradients of wastewater pollution in both estuaries, with similar results across all three trophic groups. These positive results demonstrate the potential of dead-shell assemblages for detecting spatial gradients of wastewater pollution. Highlights: δ15N from dead bivalve shells capture gradients in wastewater. Dead gastropod shells yield similar δ15N values but larger variance per site. The disparate trophic groups of these molluscan taxa did not affect δ15N values. Analysis reveals potential of dead-shell assemblages to track wastewater inputs.